ANALISIS PERBEDAAN RETURN DAN RISIKO SAHAM DENGAN DAN TANPA PERATAAN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEl - Chandra, Irwan (Widya Mandala Surabaya Catholic University, 2009)
Many researchs proved that listed companies in Indonesia Stock Exchange did income smoothing. It means that management did an effort to decrease income fluctuation to reach the favorable target, whether by the manipulation of artificial (by accounting method) or real (by transaction) variables. By this income smoothing, they expect the risk of company will be decreased. This research is designed to know whether there are any differences between income-smoothed-companies and non-incomesmoothed- companies in their returns and/or risks. Fifty five manufacture companies, became this research samples, are selec/ed by purposive sampling method. These samples are classified as income-smoothed-group and non-income-smoothed-group by Eckel's model. Thefindings showed that there is no significant difference for both stock returns and risks between income-smoothed-companies and non-income-smoothedcompanies. In the other words, although the income smoothing found in Indonesia but there is no difference for returns alld risks variable between income-smoothed-companies all d non-income-smoothed-companies.